2019
DOI: 10.1016/j.apmr.2018.07.436
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Neuropsychological Assessment of Cognitive Functioning of Adults With Lower Limb Amputation in Rehabilitation

Abstract: Findings support the need for cognitive screening at rehabilitation admission regardless of etiology. Administration of comprehensive neuropsychological assessment with a battery sensitive to vascular cognitive impairment is recommended in some cases to generate an accurate and precise understanding of relative strengths and weaknesses in cognitive functioning. Cognitive functioning is a potential intervention point for improvement of rehabilitation outcomes for those with LLA, and further research is warrante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…One-sample t-tests were used to assess whether the assessment scores of the sample differed from manualized norms. Similar analyses have been previously shown to allow for an inferential estimation of whether cognitive functioning of a sample differs from manualized norms [38] , [39] .…”
Section: Methodsmentioning
confidence: 66%
“…One-sample t-tests were used to assess whether the assessment scores of the sample differed from manualized norms. Similar analyses have been previously shown to allow for an inferential estimation of whether cognitive functioning of a sample differs from manualized norms [38] , [39] .…”
Section: Methodsmentioning
confidence: 66%
“…Many persons with lower limb amputation have reported the need to "concentrate on every step" and this may reflect increased use of cognitive resources [11]. Cognition has an impact on walking performance, and the current literature on lower limb amputation recognises this relationship [12,13,14,15,16]. Hence, it is important that outcome measures reflect the complexity of mobility in daily life by including both cognitive and environmental dimensions, and at the same time are easy and quick to administer in a clinical setting [6].…”
Section: Introductionmentioning
confidence: 99%
“…Future research in this population is critical and should aim to establish with certainty what PLLA‐specific characteristics, such as level of amputation, etiology, experience using a prosthesis, and walking automaticity, influence the interference effect that dual‐task has on balance or gait. The following list outlines important considerations for future dual‐task balance or gait research based on the trends that were observed: Cognitive function screening is important for the characterization of participant samples, yet only a minority of studies included standardized tests within their protocols even though cognitive impairment is prevalent in this population 6,20 The majority of amputations occur as a result of dysvascular disease, which can affect lower limb sensation 57 ; however, assessments for sensory integrity or proprioception were never reported even though this can confound results. Preferably, the reporting of outcome measures should include both absolute and relative (ie, dual‐task cost) performance.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 In PLLA, using a prosthesis is already cognitively demanding with many stating a cognitive burden to keeping safe 3 and having to concentrate on every step when walking. 10 Moreover, cognitive impairment, including issues related to attention, memory, and executive function, have been reported in as high as 52.6%-56.3% of PLLA 6,20 and observed to be associated with mobility problems in those with vascular-related amputations. 21 The capacity for the allocation of cognitive resources is believed to be limited in PLLA in part because of the cognitive requirements associated with the use of a prosthesis, balance and gait impairments, as well as the commonly observed presence of executive dysfunction.…”
Section: Introductionmentioning
confidence: 99%